(untitled) (Práxis Educativa, 2024)
This text addresses the financial situations of teachers in Colombia, through a documentary review with the general objective of making a comparison between the current teaching statutes in Colombia (2277 and 1278) and the proposal for the Single Teaching Statute. In addition, a systematic review of key government articles and documents was carried out, focusing on the purposes of education, function manuals, promotions and characteristics of teacher employment. The procedure included search, organization, systematization and analysis of articles, decrees and relevant Colombian laws. The bibliographic search was carried out in databases such as EBSCO, Dialnet Plus, Scielo, Google Scholar, Scopus, Web of Science. Between 95 and 100 records were identified, selecting the most relevant through critical reading, considering updates and relevance to the topic. The results show discrepancies between the decrees evidenced in promotion conditions, evaluation processes and different remunerations. It is concluded that the problems of financing and remuneration for teachers have been present throughout the history of teachers in Colombia, making it necessary to propose salary leveling and promotion processes that consider experience, academic training and the merits of the teacher. teachers to improve their salary conditions. Keywords: Teaching statutes. Public education. Teaching ranks.